THE APPLICATION OF THE BALANCED SCORECARD AS A PERFORMANCE MEASUREMENT METHOD (Case Study RSUD Lawang) - EKA CAHYA PUTRA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to determine the hospital performance using the balancedscorecard by utilizing it to develop the expected financial and non-financial aspects inconducting performance appraisals. So that, the hospital will become ideal and able toprovide customers satisfaction. Data in this research were collected in three years from 2015to 2017 by using descriptive analysis. The researcher evaluated the hospital performancebetween the periods and compare them with the previous target, and then give scoreaccording to the criteria. Data were obtained through library research and the secondary datawas obtained from Lawang Regional hospital (RSUD Lawang). Financial performancemeasurement was viewed from the achievement of revenue and cost changes, the customerperspective views of customer acquisition, customer retention, customer satisfaction, internabusiness process perspective include innovation, operational process, and response timesMeanwhile, for learning and growth perspective was viewed from employee retention andemployee training. In conclusion, four assessment perspectives are considered good enoughThe balanced scorecard is suitable to be applied to Lawang Hospital because it can provideillustrations that are more structured, comprehensive and complete so that they can presenaccurate information that can later be used for decision-making.Keyword: Performance, Balanced Scorecard, Hospital